'It all sounds very interesting, but we're just too busy!': exploring why 'gatekeepers' decline access to potential research participants with learning disabilities. Issue 1 (1st January 2020) - Williams, Peter
ABSTRACT: A growing body of literature addresses why potential research participants decline to take part in research which could improve their and others' lives. However, a neglected field of study concerns reasons why 'gatekeepers' – professional or informal supporters through whom access is negotiated – refrain from offering the people they support the chance to consider participation. This paper draws on the author's recruitment experiences in a project examining the impact of mobile technology on the lives of people with learning disabilities; his previous projects with similar cohorts, and existing literature to explore factors that contribute to gatekeeper non-compliance. A framework-analysis of fieldnotes, interview data and other documents elicited three main interconnected factors: Protection of vulnerable people and of self; Institutional factors such as policies and practices; Research factors, such as a failure to see any beneficial outcomes. Tentative suggestions are made to help improve recruitment, although initial non-responses conspire against most potential measures (such as to liaise frequently with gatekeepers). The paper concludes by opining that the most effective policy is to make sure the research itself aims to improve the lives of participants, their peers, and the wider community – and that this is clearly outlined in any approach to gatekeepers.